2007
DOI: 10.1002/cne.21528
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive morphological identification and GABA immunocytochemistry of antennal lobe local interneurons in Bombyx mori

Abstract: The insect antennal lobe (AL) is the structural and functional analog of the olfactory bulb of mammals, in which odor information is spatially and/or temporally represented by functional glomerular units. Local interneurons (LNs) play critical roles through intra- and interglomerular communication to shape the output from the AL to higher brain centers; however, the function and even the components of LNs are unclear. We have used morphological and immunocytochemical approaches to examine LNs in the silkworm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 96 publications
3
63
0
Order By: Relevance
“…These neurons are suggested to act as a general enhancer to guarantee the reliable transmission of olfactory information to the Kenyon cells of the mushroom bodies. Furthermore, a subpopulation of GABA-immunonegative local neurons has been identified in the antennal lobe of the silk moth, Bombyx mori (Seki and Kanzaki 2008). Interestingly, the LomTK-IIimmunoreactive somata reported here are slightly larger than the other local neurons (Berg et al 2007), a finding that also applies to the somata of the cholinergic local neurons in the fly (Shang et al 2007).…”
Section: Non-gabaergic Local Neuronssupporting
confidence: 54%
“…These neurons are suggested to act as a general enhancer to guarantee the reliable transmission of olfactory information to the Kenyon cells of the mushroom bodies. Furthermore, a subpopulation of GABA-immunonegative local neurons has been identified in the antennal lobe of the silk moth, Bombyx mori (Seki and Kanzaki 2008). Interestingly, the LomTK-IIimmunoreactive somata reported here are slightly larger than the other local neurons (Berg et al 2007), a finding that also applies to the somata of the cholinergic local neurons in the fly (Shang et al 2007).…”
Section: Non-gabaergic Local Neuronssupporting
confidence: 54%
“…Historically, LNs have been regarded mostly as GABAergic, inhibitory neurons, and GABAergic LNs have been reported in the AL of various insect species including A. mellifera (Schäfer and Bicker, 1986), Bombyx mori (Iwano and Kanzaki, 2005;Seki and Kanzaki, 2008), D. melanogaster (Wilson and Laurent, 2005), M. sexta (Hoskins et al, 1986), P. americana (Distler, 1989), and S. americana (Leitch and Laurent, 1996). Immunohistochemical, mass-spectrometric and physiological studies, however, showed that the LNs are biochemically a more heterogeneous population of neurons than previously thought.…”
Section: Types Of Local Interneuronsmentioning
confidence: 99%
“…6, reviewed in Schachtner et al, 2005, Seki andKanzaki, 2008;Husch et al, 2009;Carlsson et al, 2010;Chou et al, 2010;Seki et al, 2010;Neupert et al, 2012;Binzer et al, 2014;Siju et al, 2014). Comparing the different pattern of glomerulus supply via central neurons (CNs, LNs, PNs), innervation can beoccur a) only at the surface, b) scattered throughout the whole glomerulus c) or only through parts of the glomerulus, d) up to massive dense innervation of the whole or e) a distinct area of a glomerulus, or f) as described in this study, through islet like projections, which are evenly distributed throughout the glomerulus (Fig.…”
Section: Glomerular Substructuresmentioning
confidence: 99%